Corporate charitable donations under financial constraints: impact on firm performance and sustainable development in China - Cheng, Jiayang; Di Vaio, Assunta; Ong, Tze San; Teh, Boon Heng (John Wiley and Sons, 2025)
This study investigates why financially constrained Chinese firms continue to engage in substantial philanthropic giving and whether such donations yield financial and sustainability-related benefits. Positioned at the intersection of corporate social responsibility (CSR), financing constraints, and sustainable development, it examines the link between charitable contributions, firm performance, and financial constraints within the framework of the United Nations Sustainable Development Goals (SDGs), particularly SDG 8 and SDG 17. Drawing on the resource-based view and strategic charitable giving theory, the analysis uses panel data from 3856 Chinese A-share listed firms (2019–2023). Fixed Effects regression models are employed to assess the direct and moderating effects of financial constraints, while correlated random effects, alternative performance measures, and control substitutions provide robustness checks; endogeneity concerns are addressed through generalized method of moments estimation. Findings highlight that philanthropic donations enhance firm performance, but this effect weakens under financial constraints, which themselves directly reduce performance. These findings underscore the need for firms to strategically balance social commitments with financial limitations. By highlighting the moderating role of financial constraints in the donation–performance nexus, this study contributes novel empirical evidence from an emerging economy, enriching CSR research on strategic philanthropy and SDG-oriented business strategies.